The Holy Quran Revelation: Copper and it’s Astonishing benefits for Humankind from a Chemical Perspective - Labidi, Aymen (My University, 2021)
One of the most important grants of God Almighty to mankind is iron and other metals such as Copper. The reality that there is mention of copper (Cu) in the Holy Quran can be considered as a sign of it’s big importance for the human life. The fact that copper was mentioned several times either under it’s pure form or alloyed with iron might be a sign this metal is so useful for us and without it the human civilization would not progress. Verses "Ayat” of the Holy Quran are rich in meanings and words that need to be deeply managed and checked for understanding. The interpreters have begun to explain these meanings and words for thousands of years. However, as is well known, the Qur’an has lot of secrets that make it renewed and parallel to every age. In view of the modern scientific discoveries, many of the words of the Holy Quran have potential aspects of interpretation which are useful in understanding the purpose of these words. Therefore, most scholars have many scientific ideas and terms that explain the interpretation of the verses of the Quran and some of the Qur’anic terms from a scientific perspective that illustrates the scientific miracles in the Holy Quran. In this study we have addressed the Qur’anic word "Qitr" which was interpreted by the exponents as the dissolved copper in the field of Chemistry.
Keywords: Chemistry; Copper; Copper Alloy; Qitr; The Holy Quran